Comparison of long‐term survival outcome of operative vs nonoperative management of recurrent rectal cancer. (25th January 2013) - Bhangu, A.; Ali, S. M.; Cunningham, D.; Brown, G.; Tekkis, P.
Abstract Aim Complete surgical resection is considered the best treatment for recurrent rectal cancer (RRC). The aim of the study was to compare survival outcomes from operative and nonoperative patients presenting with RRC. Method Patients with RRC whose management was discussed by a tertiary referral specialist multidisciplinary team between January 2007 and August 2011 were identified from a prospectively maintained database. The primary end‐point was 3‐year overall survival. Results Of 127 patients with RRC, it was isolated to the pelvis in 105 and associated with distant disease at presentation in 22. From the time of primary surgery to first recurrence, 1‐, 3‐, 5‐ and 10‐year local recurrence rates were 22%, 72%, 85% and 96%, respectively. The number of operated patients available at 1, 2 and 3 years' follow‐up was 53, 34 and 23, respectively. Of 70 patients who underwent pelvic resection for recurrence, 64% received R0, 20% received R1 and 16% received R2 resections. Corresponding 3‐year overall survival rates were 69%, 56% and 20% (P = 0.011). There was no significant difference in survival between R2 resection and those managed nonoperatively (hazard ratio = 1.258; P = 0.579). Those undergoing surgery for pelvic recurrence affecting one or more compartments had a worse prognosis than those with single‐compartment involvement (hazard ratio = 2.640; P = 0.027). Three‐year local recurrence‐free survival was 80% with R0 resection vs 60% with R1 resection. Conclusion Most recurrences occur within 5 years of primary surgery, although some occur up to 10 years later. R0 resection is the treatment of choice. There was no survival benefit of R2 resection over nonresected recurrences.